MYTH, WORLD TIME AND SPACE MODELS IN THE POSTMODERN WORKS OF V. PELEVIN - Dohnal, Josef; Abaganova, Assel (Porównania, 2019)
This article focuses on one of the themes of Pelevin’s creative work – the category of myth. The myth is investigated in all its forms, variations and transformations from classical mythology (God Ra) to modern social, political to vampire mythology. Modern mythology is an instrument of socialization of a mass man, and manipulation of his consciousness. Myth, by virtue of many times repeated frequency, changes the category of time in the unfolding of the plot in the works of postmodernists. The problem of determining the status and role of myth in the work of V. Pelevin is studied. Pelevin uses in his novels such a feature of his poetics as «neomythologism» – the intertextual borrowing of certain elements of archaic structures of myths or meta-stories. Mythological time replaces the objective historical time, since actions and events are represented as prototypes in the novel.